The Effectiveness of English Listening Application to Improve the Students’ Listening Ability - Ramadhan, Rafiuddin; Purnama, Atmaranie Dewi; Rahman, Hardianto; Nurhayati, R (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study aimed to determine the effectiveness of English listening applications in improving the English listening proficiency of students from the TBI 2020 cohort at IAIM Sinjai. Employing a classroom action research methodology, the study involved a population of 25 students. Data were collected through observation and testing, with the N-Gain formula utilized for data analysis. The findings indicate that the implementation of an English listening application significantly and positively improved students' listening skills. This improvement is evident from the substantial increase in student scores: the average pre-test score was 11.176, while the average post-test score remarkably rose to 73.376. The N-Gain analysis confirmed these results, placing the improvement in the